Diversification of agriculture practices as a response to climate change impacts among farmers in low-income countries: a systematic literature review - Mohamed Shaffril, Hayrol Azril; Abu Samah, Asnarulkhadi; Samsuddin, Samsul Farid; Ahmad, Nobaya; Tangang, Fredoline; Ahmad Sidique, Shaufique Fahmi; Abdul Rahman, Haliza; Burhan, Nik Ahmad Sufian; Arif Shah, Jasmin; Khalid, Nurul Amiera (Elsevier, 2024)
The primary objective of this study is to systematically review the literature on the diversification of agriculture practice as one of the many ways farmers in low-income countries can respond and adapt to the worsening impacts of climate change. To ascertain the rigor in its methodology, this systematic literature review (SLR) adhered to guidelines outlined in RepOrting standards for Systematic Evidence Syntheses (ROSES); the research question was formulated based on the mnemonics of Population, Interest, and Context (PICo), the inclusion and exclusion criteria were based on timeline publication, document type, language, low-income countries and focused on reviewing empirical evidence studies; the quality was appraised based on Mixed Method Appraisal Tools (MMAT), while data extraction and analyses were executed using thematic analysis. The analytical outcomes yielded three main themes. First is the theme related to crops and varieties-related strategies, which consist of four sub-themes: early maturing crops, use of the drought-tolerant variety, abandoning crops, and introduction of new crop/crop rotation/crop diversity/mixed crop. The second theme is soil and water conservation techniques, which later produced another six sub-themes, namely the use of organic/inorganic fertilizer, water harvesting, irrigation and drainage, tree planting and agroforestry, terracing/contour farming to prevent soil erosion, mulching/stone barriers and agriculture mechanisation related activities. The last theme is planting-related strategies, which consist of three sub-themes: rescheduling the planting calendar, increasing pesticide/herbicide/integrated pest management, and selecting and expanding new areas. Referring to this SLR, there is a pressing need to facilitate farmers facing inadequate resources to adapt effectively to environmental and other change forms. Upon comprehending the present adaptation practices used by farmers, interested parties may offer ideas to strategize effective adaptation plans tailored to farmers’ needs, abilities, and interests across low-income countries.